Clinical guide to musculoskeletal palpation - Masaracchio, Michael 1976-; Frommer, Chana (Human Kinetics, 2014)
A guide that is supported by photographs demonstrating palpation techniques of surface body landmarks and will assist students and healthcare professionals in becoming proficient in the surface palpation techniques which are a prerequisite for working in the manual therapy professions